2019
DOI: 10.3389/fphar.2019.00693
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine and Vortioxetine Reverse Depressive-Like Phenotype and Memory Deficits Induced by Aβ1-42 Oligomers in Mice: A Key Role of Transforming Growth Factor-β1

Abstract: Depression is a risk factor for the development of Alzheimer’s disease (AD), and the presence of depressive symptoms significantly increases the conversion of mild cognitive impairment (MCI) into AD. A long-term treatment with antidepressants reduces the risk to develop AD, and different second-generation antidepressants such as selective serotonin reuptake inhibitors (SSRIs) are currently being studied for their neuroprotective properties in AD. In the present work, the SSRI fluoxetine and the new multimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 65 publications
1
52
0
Order By: Relevance
“…It has been shown in vivo that the administration of TGF-β1 is able to protect against Aβ-induced neuroinflammation and neurodegeneration [84][85][86], whilst mutations of the TGF-β1 gene in mice lead to death from multifocal inflammation and autoimmune disorders in internal organs [87,88]. Additionally, a significant deficit of TGF-β1, paralleling memory deficits and depressive-like phenotype, has been found in the hippocampus of Aβ-injected mice [89]. Very recently, the ability of carnosine to protect brain macrophages and neurons against Aβ-induced cell toxicity by increasing TGF-β1 expression and secretion has been proposed [23].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in vivo that the administration of TGF-β1 is able to protect against Aβ-induced neuroinflammation and neurodegeneration [84][85][86], whilst mutations of the TGF-β1 gene in mice lead to death from multifocal inflammation and autoimmune disorders in internal organs [87,88]. Additionally, a significant deficit of TGF-β1, paralleling memory deficits and depressive-like phenotype, has been found in the hippocampus of Aβ-injected mice [89]. Very recently, the ability of carnosine to protect brain macrophages and neurons against Aβ-induced cell toxicity by increasing TGF-β1 expression and secretion has been proposed [23].…”
Section: Discussionmentioning
confidence: 99%
“…Stress exposure also leads to an impairment of TGF-β1 signaling in different brain regions (hippocampus, cortex, and hypothalamus) (You et al, 2011;Caraci et al, 2015). This impairment has been connected to the onset of a depressive-like phenotype in mice (Torrisi et al, 2019). Lastly, a correlation between reduced TGF-β1 plasma levels, depression severity, and treatment resistance in MDD has been proved (Sutcigil et al, 2007;Caraci et al, 2018a).…”
Section: The Pathophysiology Of Depression: the Role Of Neurotrophic mentioning
confidence: 97%
“…Likewise, a decrease of TGF-β1 levels has been observed in hippocampus and cortex of animal models of depression (Yu et al, 2011); furthermore, several studies carried out in depressed patients have demonstrated that plasma TGF-β1 levels are reduced and correlate with depression severity (Myint et al, 2005;Rush et al, 2016). A chronic treatment with first-and second-generation antidepressants rescues BDNF levels in different preclinical models of depression (Duman and Monteggia, 2006), while selective serotonin reuptake inhibitors (SSRIs) drugs and the new multimodal antidepressant vortioxetine are able to reverse the depressive-like phenotype and memory deficits induced by amyloid-β (Aβ) in mice by the rescue of TGF-β1 1 https://www.who.int/health-topics/depression#tab=tab_1 (Torrisi et al, 2019). Furthermore, antidepressant drugs exert immunoregulatory effects reducing the production of proinflammatory cytokines and stimulating the synthesis of TGF-β1 in depressed patients (Sutcigil et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 is a neurotrophic factor whose deficit exerts a key role in AD. A selective impairment of TGF-β1 pathway is present in early AD, both in the AD brain (121,122) and in AD animal models (71,123,124). This deficit seems to critically contribute to neuroinflammation in AD brain.…”
Section: Cellular and Molecular Neuroinflammatory Pathways In Alzheimmentioning
confidence: 98%
“…Aβ, amyloid beta; Aβ 1−42 , 42-amino acid-long amyloid beta peptide; BDNF, brain-derived neurotrophic factor; IL-1β, interleukin-1 beta; MMP-9, metalloprotease-9; NGF, nerve growth factor; mNGF, mature nerve growth factor; proNGF, precursor of the nerve growth factor; RNS, reactive nitrogen species; ROS, reactive oxygen species; TGF-β, transforming growth factor-beta; TNF-α, tumor necrosis factor-alpha. produce and release proinflammatory cytokines (14,68) and also by interfering with the synthesis of anti-inflammatory cytokines, for instance the transforming growth factor-beta 1 (TGF-β1) ( Figure 2) (69)(70)(71). This early proinflammatory process is characterized by neuronal and microglia-derived cytokines and chemokines as well as by mobilization of microglia toward Aβ-burdened neurons (Figure 2) (19,72).…”
Section: The Role Of Microgliamentioning
confidence: 99%